2008
DOI: 10.1002/ajmg.a.32233
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects in spinal muscular atrophy type I: A clinical report of two siblings and a review of the literature

Abstract: A newborn girl presented with asphyxia, joint contractures and diminished spontaneous movements. Echocardiography showed hypoplastic left heart. Spinal muscular atrophy type I (SMA I) was diagnosed by detecting a homozygous deletion in the survival motor neuron 1 gene (SMN1). In the first trimester of a subsequent pregnancy, SMA I, hypoplastic left heart, and contractures were identified again. Congenital heart defects (CHD) have now been reported in 20 patients with SMA I, including three previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…42,43,64 In humans, cardiac involvement has been described in the form of congenital malformations (predominantly SMA type I) and case reports of cardiomyopathy (predominantly SMA type III). 41,44,[65][66][67] The question remains whether our observations are due to autonomous nerve involvement or muscle development or affection. We found that motoneuron endplate size in the TVA muscle from affected late-stage animals was smaller than that in P0 animals reflecting progressive neurodegeneration.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…42,43,64 In humans, cardiac involvement has been described in the form of congenital malformations (predominantly SMA type I) and case reports of cardiomyopathy (predominantly SMA type III). 41,44,[65][66][67] The question remains whether our observations are due to autonomous nerve involvement or muscle development or affection. We found that motoneuron endplate size in the TVA muscle from affected late-stage animals was smaller than that in P0 animals reflecting progressive neurodegeneration.…”
Section: Discussionmentioning
confidence: 92%
“…The remaining 50% are healthy SMA carriers (Smn þ / À ; SMN2 tg/0 ) and used as controls. 30 Recent reports suggest that abnormal heart development in mice and human [41][42][43][44] as well as defects in skeletal muscle 45 and skeletal muscle vasculature 46 of mice are part of the phenotype and that SMA may be not a pure motoneuron disease. In addition, decreased levels of hepatic insulin-like growth factor binding protein acid labile subunit 18 possibly account for some of the dwarfism observed consistently across different SMA mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Of therapeutic relevance, increasing the excitability of motor circuits through the pharmacological inhibition of K + channels ameliorated SMA in animal models [93]. Further evidence of the wider impact of SMN deficiency in disease pathogenesis comes from abnormalities in Schwann cells, skeletal muscle, heart, bone, pancreas, liver, hippocampus, thalamus, and the vascular system [94][95][96][97][98][99][100][101]. Controversy remains over the relative contribution of organ systems other than the motor neuron in SMN1-related SMA pathogenesis.…”
Section: Insights Into Smn1-related Sma Pathogenesismentioning
confidence: 99%
“…Additional clinical reports of individuals and siblings have also described an association between SMA type 1 disease severity and heart abnormalities [131][132][133]. It has thus been proposed that the combination of SMA and congenital heart defects may be exclusive to type 1 SMA [131].…”
Section: Cardiac Musclementioning
confidence: 99%
“…It has thus been proposed that the combination of SMA and congenital heart defects may be exclusive to type 1 SMA [131].…”
Section: Cardiac Musclementioning
confidence: 99%